Pregnane X receptor activation induces FGF19-dependent tumor aggressiveness in humans and mice - Hongwei Wang; Madhukumar Venkatesh; Hao Li; Regina Goetz; Subhajit Mukherjee; Arunima Biswas; Liang Zhu; Andreas Kaubisch; Lei Wang; James Pullman; Kathleen Whitney; Makoto Kuro-o; et al. (The Journal of Clinical Investigation, 2011)
The nuclear receptor pregnane X receptor (PXR) is activated by a range of xenochemicals, including chemotherapeutic drugs, and has been suggested to play a role in the development of tumor cell resistance to anticancer drugs. PXR also has been implicated as a regulator of the growth and apoptosis of colon tumors. Here, we have used a xenograft model of colon cancer to define a molecular mechanism that might underlie PXR-driven colon tumor growth and malignancy. Activation of PXR was found to be sufficient to enhance the neoplastic characteristics, including cell growth, invasion, and metastasis, of both human colon tumor cell lines and primary human colon cancer tissue xenografted into immunodeficient mice. Furthermore, we were able to show that this PXR-mediated phenotype required FGF19 signaling. PXR bound to the FGF19 promoter in both human colon tumor cells and “normal” intestinal crypt cells. However, while both cell types proliferated in response to PXR ligands, the FGF19 promoter was activated by PXR only in cancer cells. Taken together, these data indicate that colon cancer growth in the presence of a specific PXR ligand results from tumor-specific induction of FGF19. These observations may lead to improved therapeutic regimens for colon carcinomas.